Biographical traces of educational experiences in the construction of political subjectivities - Piani Mailhos, Miriam Monica (IE Revista de Investigación Educativa de la REDIECH, 2019)
This research is located on higher education institutions of Bariloche. Starting from the complex relationship that exists between the western colonizing project and the educational processes, from a decolonial perspective in dialogue with critical theorical categories, it is inquired in the educational experiences of teachers, students and graduates; recovering traces of colonization, in terms of ways of being-living-doing in the world and knowing; and clues as breakdowns in the construction of political subjectivities. Based on a qualitative inquiry, it can be understood that colonization and decolonization processes are given simultaneously, an although, the experiences that breakdown the hegemony, are present in formal and informal areas, being more frequent in the latter. We point out that in all of them the subject is affected in the corporal hermeneutical transits or remained aesthetically affected. Some constructions teachings that are visible as potential breakdowns, do not have the impact that we are looking for. Concerning the pedagogical processes regulations policies, in some cases they facilitate emancipations, and in other cases, colonizations are reproducing.